Visible-Light-Induced C–C Coupling Reaction to Synthesize Bipyridine From 3-Cyano-1,4-Dihydropyridines - Chen, Shijun; Zhong, Qidi; Zhu, Hao; Liu, Chunyan; Zhuang, Pengyu; Sun, Wuji (Frontiers in Chemistry, 2020)
A concise and efficient photocatalytic C-C coupling of 1-benzyl-3-cyano-1,4-dihydropyridine for synthesis of 1,1'-dibenzyl-3,3'-dicyano-1,1',4,4'-tetrahydro-4,4'-bipyridine is described. The reporter system provides a novel technique that facilitates synthesis of C-C coupling derivatives without addition of transition metals and oxidants or other additives. A plausible synthetic pathway is proposed, and the coupling product was characterized via nuclear magnetic resonance spectroscopy (1H and 13C NMR), high-resolution electrospray ionization mass spectrometry (ESI-HRMS) and X-ray analyses.